Analisis Keamanan Jaringan Pada Layanan Wifi Dengan Menggunakan Wireshark - Ariel Teza Permana, Ariel; Fajar Ramadhan, Albi (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2025)
WiFi is an acronym for Wireless Fidelity. WiFi can be said to be a technology for exchanging data by utilizing radio waves (wireless) which can be used by several electronic devices such as computers, smartphones, tablets, and so on. WiFi has various advantages that make this technology a prima donna for the community. In computer networks, the term protocol is known, which is a set of rules/procedures or standards used to transmit data between electronic devices. Currently, information security issues are becoming important, especially the process of tapping information (sniffing) on computer networks is becoming increasingly common, both for positive and reverse uses. In this study, the sniffing process was used to obtain username and password information. The sniffing process is done using the Wireshark software. Wireshark is a software application that is used to view and analyze data packets passing on a network. Wireshark is a network packet analysis program that will capture network packets and try to display data from a packet as detailed as possible. The Wireshark software performs the process of capturing data on the Wireless interface, then observes the captured results which contain POST data containing username and password on HTTP. From the results of the research conducted, it was found that using Wireshark can intercept data carried out on computer networks, this results in the loss of one of the security characteristics, namely privacy and confidentiality.